2018
DOI: 10.1016/j.oceaneng.2018.03.047
|View full text |Cite
|
Sign up to set email alerts
|

Flexible hydrofoil optimization for the 35th America's Cup with constrained EGO method

Abstract: This paper investigates the use of constrained surrogate models to solve the multi-design optimization problem of a flexible hydrofoil. The surrogate-based optimization (EGO) substitutes the complex objective function of the problem by an easily evaluable model, constructed from a limited number of computations at carefully selected design points. Associated with ad-hoc statistical strategies to propose optimum candidates within the estimated feasible domain, EGO enables the resolution of complex optimization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…Another study also showed that the position of the foil in the vertical direction also had an effect on hydrodynamic performance [22]. The optimum position of hydrofoil was when it was fully submerged at an angle of 36 degrees at the speed 30 knots [23]. There are still very few researchers investigating the effect of the hydrofoil position in the horizontal direction.…”
Section: Introductionmentioning
confidence: 99%
“…Another study also showed that the position of the foil in the vertical direction also had an effect on hydrodynamic performance [22]. The optimum position of hydrofoil was when it was fully submerged at an angle of 36 degrees at the speed 30 knots [23]. There are still very few researchers investigating the effect of the hydrofoil position in the horizontal direction.…”
Section: Introductionmentioning
confidence: 99%
“…Other research in morphing hydrofoils can be found in the works from Garg et al (2015) and Sacher et al (2018) in which computational fluid dynamics and structural analysis methods have been used together for coupled hydrodynamicstructural solutions. In other research, a passive trailing edge morphing hydrofoil for sailing applications has been proposed to extend the range of efficiency.…”
Section: Morphing Structures Applications Of Fig 7 Ship With Morphmentioning
confidence: 99%
“…The objective of the optimization is to minimize the hydrofoil drag force at selected conditions (forward speed and lifting force) while ensuring non-cavitating flows. The complete description of the optimization problem and the hydrodynamical analysis of the optimized hydrofoil are not provided in this paper, which focuses on the method; interested readers can refer to [42]. The original optimization problem proposed in [42] involved 11 design variables describing the shape and elastic characteristics of the foil flexible trailing edge, as schematically illustrated in Figure 11.…”
Section: Application To Flexible Hydrofoil Optimization 41 Optimizatmentioning
confidence: 99%
“…The complete description of the optimization problem and the hydrodynamical analysis of the optimized hydrofoil are not provided in this paper, which focuses on the method; interested readers can refer to [42]. The original optimization problem proposed in [42] involved 11 design variables describing the shape and elastic characteristics of the foil flexible trailing edge, as schematically illustrated in Figure 11. In the present work, the number of design variables is reduced to 5 in order to maintain reasonable computational times and to allow As mentioned before, the optimization concerns the minimization, for 4 conditions, of the hydrofoil drag coefficients C Di=1,...,4 .…”
Section: Application To Flexible Hydrofoil Optimization 41 Optimizatmentioning
confidence: 99%